The quasitransitive relation x≤5/4y. Its symmetric and transitive part is shown in blue and green, respectively.
The mathematical notion of quasitransitivity is a weakened version of transitivity that is used in social choice theory and microeconomics. Informally, a relation is quasitransitive if it is symmetric for some values and transitive elsewhere. The concept was introduced by Sen (1969) to study the consequences of Arrow's theorem.
Formal definition
A binary relation T over a setX is quasitransitive if for all a, b, and c in X the following holds:
If the relation is also antisymmetric, T is transitive.
Alternately, for a relation T, define the asymmetric or "strict" part P:
Then T is quasitransitive if and only if P is transitive.
Examples
Preferences are assumed to be quasitransitive (rather than transitive) in some economic contexts. The classic example is a person indifferent between 7 and 8 grams of sugar and indifferent between 8 and 9 grams of sugar, but who prefers 9 grams of sugar to 7.[1] Similarly, the Sorites paradox can be resolved by weakening assumed transitivity of certain relations to quasitransitivity.
Properties
A relation R is quasitransitive if, and only if, it is the disjoint union of a symmetric relation J and a transitive relation P.[2]J and P are not uniquely determined by a given R;[3] however, the P from the only-if part is minimal.[4]
As a consequence, each symmetric relation is quasitransitive, and so is each transitive relation.[5] Moreover, an antisymmetric and quasitransitive relation is always transitive.[6]
The relation from the above sugar example, {(7,7), (7,8), (7,9), (8,7), (8,8), (8,9), (9,8), (9,9)}, is quasitransitive, but not transitive.
A quasitransitive relation needn't be acyclic: for every non-empty set A, the universal relationA×A is both cyclic and quasitransitive.
A relation is quasitransitive if, and only if, its complement is.
Similarly, a relation is quasitransitive if, and only if, its converse is.
^The naminig follows Bossert & Suzumura (2009), p.2-3. — For the only-if part, define xJy as xRy ∧ yRx, and define xPy as xRy ∧ ¬yRx. — For the if part, assume xRy ∧ ¬yRx ∧ yRz ∧ ¬zRy holds. Then xPy and yPz, since xJy or yJz would contradict ¬yRx or ¬zRy. Hence xPz by transitivity, ¬xJz by disjointness, ¬zJx by symmetry. Therefore, zRx would imply zPx, and, by transitivity, zPy, which contradicts ¬zRy. Altogether, this proves xRz ∧ ¬zRx.